Effect of preharvest treatments on the changing of dry matter and total soloube solids of stored six onion varieties - Gad-Allah, Soliman Omar; Mohamed, Saleh Abd EL-Rehim; Abd EL-Wahed, Ahmed Mohamed Ahmed (Al-Mukhtar Journal of Sciences, 2008)
Six onion varieties were evaluated under four planting spaces at the experimental farm of Faculty of Agriculture, Omar Al-Mokhtar University, Al-Beida, Al-Gabal El-Akhdar region, during the two successive seasons of 2006 and 2007. The tested Varieties were Red Amposta , El-Behairy, Red Creole, Giza 20, Giza 6 and Texas Early Grano. Plant distance between seedlings were 7.5, 10, 12.5 and 15cm, which equal 532,400,320,126 thousands seedlings per hectar,respectively. The six varieties, four spacings, storing method and their various interactions were compared in respect to the percentages of total solibale solids and dry matter of bulbs at harvesting and during storage for six monthes under room and cold storage conditions at zero 0˚c. The obtained results could be summarized as follow: Cold storage significantly increased bulbs dry matter content comparing with room (ambient temp.) storage, however the storage methods had no effect on bulb TSS content allover the storage periods, in the two studied seasons. Planting at 7.5 cm significantly increased bulb dry matter content at all storage periods (180 days), in the two seasons, comparing to the wider spacings, which were not significantly differed. The studied varieties varied significantly concerning with bulbs dry matter and TSS contents, at all storage periods of the two seasons. The highest variety in its dry matter content at beginning and end storage period was Red Amposta (22.30 and 28.89 ,respectively), whereas, Texas Early Grano had the lowest content (11.56, 16.29%, respectively). The remained varieties recorded intermediate values. Giza 20 variety occupied the first possion in its TSS content at the beginning of storage (13.39%) whereasTexas Early Grano was the latest one (7.44%). Giza 6, Red Amposta, and El-Beihary did not differ in their TSS content, at all storage periods as well as Giza 20, at some storage periods. The narowest spacing (7.5 cm) significantly decreased bulb dry matter content, either in ambient or cold storage ,as compared with the wider spacings which were not significantly differed in their effects. Whereas, the opposite was true , regarding the total soluble solids through the storage periods. The storage methods affected differentially the bulb dry matter and TSS contents, depending on varieties and storage periods. The 7.5 and 10 cm spacings were the effective factor within all varieties, at all storage periods in two seasons, which reduced and increased, respectively, the dry matter content of bulbs. Plant densities had no effect on TSS content of Red Amposta bulbs at all storage periods, but affected differentialy on the other varieties. The triple interaction had significant and different effects on the percentages of dry matter, TSS.